Atomic-scale assessment of the crystallization onset in silicon carbonitride. Issue 12 (October 2015) - Mera, Gabriela; Ishikawa, Ryo; Ionescu, Emanuel; Ikuhara, Yuichi; Riedel, Ralf
Abstract Within the present study, atomic-scale electron microscopy investigation on the crystallization behavior of polysilylcarbodiimide-derived SiCN was performed. The as-prepared SiCN sample was found to be homogeneous and consisted of amorphous silicon nitride nano-domains dispersed within an amorphous, highly entangled graphene-like carbon matrix. Annealing of the sample at 1400 °C induced a slight increase of the ordering of the carbon phase. Additionally, the crystallization onset of the silicon nitride has been observed for the first time. In the sample annealed at 1400 °C small nano-clusters with average sizes of 0.8, 1.5 and 2.1 nm (consisting of 30, 180 and 570 atoms, respectively; corresponding to Si12N18, Si72N108 and Si228N342) were imaged and assigned to α-silicon nitride. The crystallization of the amorphous silicon nitride phase into α-Si3N4 is thought to occur via diffusion of Si and N, which rely on the presence of large number of dangling bonds in the amorphous SiCN sample.